Correlation of Alvarado score for acute appendicitis with pathological acute appendicitis - Sonawane, Ratnadip S.; Jatkar, Girish L.; Chaudhari, Milind S. (International Surgery Journal, 2016)
Background:The vermiform appendix is important in surgery due to its propensity for inflammation which results in the clinical syndrome known as acute appendicitis. Approximately 7% of the population will have appendicitis in their life time, with the peak incidence occurring between 10 and 30 years. There occur numerous instances in the practice of medicine which demand of the physician expert diagnostic skill, sound judgment, quick and competent treatment. In 1986, Alvarado evaluated common clinical and laboratory findings in relation to pathologically proven acute appendicitis. Alvarado score had sensitivity of 81% and a specificity of 74%. The main objective is to study efficacy of Alvarado score in diagnosis of acute appendicitis Methods: This is a randomized study comprising of 138 patients of suspected acute appendicitis. The patients with suspected acute appendicitis are evaluated on the basis of the Alvarado scoring system on admission and divided into 3 groups (A, B and C). Patients were treated based on the clinical impression, following all standard surgical principals. The surgical specimen was sent for histopathological examination for confirmation of diagnosis. Data was collected, recorded and then processed. Results:Out of total 138 patients included in study, 117 patients were subjected to emergency appendectomy. 111 patients out of 117 patients operated were true positive for acute appendicitis, confirmed by histopathology report. Rest 6 patients out of 117 had normal appendix on histopathology. The Sensitivity of Alvarado score was 92.79%, specificity was 77.77%, positive predictive value was 94.49% and negative predictive value was 72.14% in our study. Conclusions:Alvarado scoring system is a good diagnostic indicator for acute appendicitis. It helps in reducing the number of negative appendicectomies.